ANALISIS PENGARUH MOTIVASI TERHADAP KINERJA PEGAWAI PADA KANTOR DINAS PERINDUSTRIAN DAN PERDAGANGAN KABUPATEN KUTAI TIMUR - Fitriyani, Fitriyani (PREDIKSI, 2016)
The purpose of the research is to know whether there is a motivation influence on the performance of the employeesÂ  of Dinas Perindustrian & Perdagangan Kabupaten East Kutai. the analysis used a simple Linier regression test. Using the sampling method is determined by the number of samples as much as 45 employees of Dinas Perindustrian & Perdagangan Kabupaten East Kutai, the data obtained through the questioner.The results of the simple regression analysis between the variables motivation and performance of employees obtained equation Y = 1.83 0,5127 X. Then the value of the correlation r of 0,616. After the results of the analysis of the compared with r table (table critical price) where N = 45 with equal significance 0.05, r count the empirical greater than r table (0,616>0,3059). Thus the hypothesis of work (hi) accepted the truth and reject the hypothesis of zero (ho) It means there is no influence between work motivation with the performance employeesÂ  of Dinas Perindustrian & Perdagangan Kabupaten East Kutai.